A new architecture of INC-fuzzy hybrid method for tracking maximum power point in PV cells. (1st September 2018) - Danandeh, M.A.; Mousavi G, S.M.
Highlights: Propose a new fuzzy based hybrid method for tracking maximum power point. Achieving high speed, high accuracy, inexpensive costs, less oscillation using the proposed method. Decreasing the number of rules of fuzzy MPPT by using of INC method concept. The life cycles of converter will increase in comparison to similar methods. Abstract: The importance and necessity of energy for human societies are so clear but the traditional sources of energy are in decline and also according to many reports using of them causes many problems like environmental pollution. The sun is one of the renewable sources of energy which can be considered as one of the good solutions for energy problem. PV cells are usually expensive and have low efficiency so extracting the maximum power of PV cells is one of the most important parts of the solar energy studies. Using of fuzzy logic is one of the most accurate methods for tracking maximum power point but this method has a big problem: high price. By considering this note that reduction in number of fuzzy rules can extremely reduce the costs, this paper is going to combine the INC method and fuzzy logic in new architecture in order to reduce the number of fuzzy rules and costs without missing the accuracy. In other words the proposed architecture has the advantages of pure fuzzy system like high speed and accuracy while its cost is so fewer and also it is simpler to implement. In comparison between proposed architecture and existing INC-fuzzy method, the results show that the new architecture is so faster and also using of it will reduce the number of switching in converters which means the life time of converters will increase.